Reprogramming lipid metabolism as potential strategy for hematological malignancy therapy - Zhang, Leqiang; Chang, Ning; Liu, Jia; Liu, Zhuojun; Wu, Yajin; Sui, Linlin; Chen, Wei (Frontiers in Oncology, 2022)
Hematological malignancies are one of the most lethal illnesses that seriously threaten human life and health. Lipids are important constituents of various biological membranes and substances for energy storage and cell signaling. Furthermore, lipids are critical in the normal physiological activities of cells. In the process of the lethal transformation of hematological malignancies, lipid metabolism reprogramming meets the material and energy requirements of rapidly proliferating and dividing tumor cells. A large number of studies have shown that dysregulated lipid metabolism, commonly occurs in hematological malignancies, mediating the proliferation, growth, migration, invasion, apoptosis, drug resistance and immune escape of tumor cells. Targeting the lipid metabolism pathway of hematological malignancies has become an effective therapeutic approach. This article reviews the oncogenic mechanisms of lipid metabolism reprogramming in hematological malignancies, including fatty acids, cholesterol and phospholipids metabolism, thereby offering an insight into targeting lipid metabolism in the treatment of hematological malignancies.